Propuesta de planeación estratégica basada en el balanced scored card (cmi) colegio militar “Eloy Alfaro” ubicado en el distrito metropolitano de Quito - Rueda Vaca, Edison Luis (2015)
This research aims to provide an overview of the institution through the application and implementation of the strategic plan in order to improve administrative management in the institution, improve the administrative aspects , financial, human , and other academic resources basic areas that have the Soul Master of the Ecuadorian Army ; It is the first center of academic studies in military training. The Military “Eloy Alfaro” College in Quito, Pichincha province; they have set targets, which managed to achieve by the methods, techniques and procedures used throughout the process. He proceeded to perform market segmentation, in which students were chosen, administrative staff and teachers of the institution, the same who were surveyed according to the questionnaire established , the data that shed are from a joint of standardized questions to a representative sample, in this case 224 students , 10 administrative and 44 teachers , in order to know the state of opinion, features or specific facts , the same as were used for the preparation of the SWOT matrix. The methods and techniques allowed to obtain information relating to the research, to further process this information, in order to strengthen the objectives. For the analysis of internal factors, interviews and surveys they were applied to the relevant areas of the organization raise the matrix allowing internal factors (strengths and weaknesses) were performed. And external factors (opportunities and threats) were carried out by another survey, and methodology of Porter. In technical research study and according to the installed capacity is proposed to implement the Balanced Score Card (Scorecard) The importance of the feasibility of this research for the benefit of strategic planning in addressing the mission and vision of the College to achieve competitive levels of scientific excellence humanist and future-oriented military leadership values serving peace prosperity and freedom. Finally, conclusions and recommendations are made known to all staff in order to implement part of the institution were made